Oily Wastewater Treatment Using Expanded Beds of Activated Carbon and Zeolite - A. M. Mohammed, Sawsan; Faisal, Ibtihage; M. Alwan, Maha (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
Two types of adsorbents were used to treat oily wastewater, activated carbon and zeolite. The removal efficiencies of these materials were compared to each other. The results showed that activated carbon performed some better properties in removal of oil. The experimental methods which were employed in this investigation included batch and column studies. The former was used to evaluate the rate and equilibrium of carbon and zeolie adsorption, while the latter was used to determine treatment efficiencies and performance characteristics. Expanded bed adsorber was constructed in the column studies. In this study, the adsorption behavior of vegetable oil (corn oil) onto activated carbon and zeolite was examined as a function of the concentration of the adsorbate, contact time, adsorbent dosage and amount of coagulant salt(calcium sulphate) added . The adsorption data was modeled with Freundlich and Langmuir adsorption isotherms. and it was found that the adsorption process on activated carbon and zeolite fit the Freundlich isotherm model. The amount of oil adsorbed increased with increasing the contact time, but longer mixing duration did not increase residual oil removal from wastewater due to the coverage of the adsorbent surface with oil molecules. It was found that as the dosage of adsorbent increased, the percentage of residual oil removal also increased. The effects of adsorbent type and amount of coagulant salt(calcium sulphate) added on the breakthrough curve were studied in details in the column studies. Expanded bed behavior was modeled using the Richardson-Zaki correlation between the superficial velocity of the feed stream and the void fraction of the bed at moderate Reynolds number.